Up-conversion luminescence of rare earth-doped KGd(WO4)2 phosphors for tunable multicolour light generation. (11th August 2017) - Kasprowicz, D.; Głuchowski, P.; Maciejewska, B. M.; Chrunik, M.; Majchrowski, A.
Abstract : A series of novel KGd(WO4 )2 crystalline powders doped with Yb 3+ /Tm 3+, Yb 3+ /Er 3+ and Yb 3+ /Ho 3+ were synthesized using a modified Pechini method. Abstract : A series of novel KGd(WO4 )2 crystalline powders doped with Yb 3+ /Tm 3+, Yb 3+ /Er 3+ and Yb 3+ /Ho 3+ were synthesized using a modified Pechini method. The monoclinic structure of these compounds was confirmed by XRD. The luminescence properties were investigated by measuring up-conversion luminescence spectra and decay curves. KGd(WO4 )2 crystalline powders doped with Yb 3+ /Tm 3+, Yb 3+ /Er 3+ and Yb 3+ /Ho 3+ exhibit effective multicolour up-conversion luminescence in the VIS and NIR spectral ranges under 980 nm excitation. The vibrational properties of the materials were investigated using μ-Raman spectroscopy. The assistance of low energy phonons of the KGd(WO4 )2 matrix in the energy transfer processes between the excited manifolds of the Yb 3+, Er 3+, Tm 3+ and/or Ho 3+ ions during the up-conversion process was discussed. These results indicate that KGd(WO4 )2 powders doped with selected Tm 3+, Er 3+, Ho 3+ and Yb 3+ ions may be potentially used as single-component multicolour or white emission phosphors.